A comparison of DSM‐5 and DSM‐IV agoraphobia in the World Mental Health Surveys. Issue 6 (6th February 2019) - Roest, Annelieke M.; de Vries, Ymkje Anna; Lim, Carmen C. W.; Wittchen, Hans‐Ulrich; Stein, Dan J.; Adamowski, Tomasz; Al‐Hamzawi, Ali; Bromet, Evelyn J.; Viana, Maria Carmen; de Girolamo, Giovanni; Demyttenaere, Koen; Florescu, Silvia; et al.
Abstract: Background: The Diagnostic and Statistical Manual of Mental Disorders, version 5 ( DSM ‐5) definition of agoraphobia (AG) as an independent diagnostic entity makes it timely to re‐examine the epidemiology of AG. Study objective was to present representative data on the characteristics of individuals who meet DSM ‐IV criteria for AG (AG without a history of panic disorder [PD] and PD with AG) but not DSM ‐5 criteria, DSM ‐5 but not DSM ‐IV criteria, or both sets of criteria. Methods: Population‐based surveys from the World Mental Health Survey Initiative including adult respondents ( n = 136, 357) from 27 countries across the world. The Composite International Diagnostic Interview was used to assess AG and other disorders. Results: Lifetime and 12‐month prevalence estimates of DSM ‐5 AG (1.5% and 1.0%) were comparable to DSM ‐IV (1.4% and 0.9%). Of respondents meeting criteria in either system, 57.1% met criteria in both, while 24.2% met criteria for DSM ‐5 only and 18.8% for DSM ‐IV only. Severe role impairment due to AG was reported by a lower proportion of respondents who met criteria only for DSM ‐IV AG (30.4%) than those with both DSM ‐5 and DSM ‐IV AG (44.0%; χ 2 1 = 4.7; P = 0.031). The proportion of cases with any comorbidity was lower among respondents who met criteria only for DSM ‐IV AG (78.7%) than those who met both sets (92.9%; χ 2 1 = 14.5; P < 0.001). Conclusions: This first large survey shows that, compared to the DSM ‐IV, the DSM ‐5 identifies a substantial group of new cases with AG, while the prevalence rate remains stable at 1.5%. Severity and comorbidity are higher in individuals meeting DSM ‐5 AG criteria compared with individuals meeting DSM ‐IV AG criteria only.